Developing Printed English Grammar Materials For Grade Seven Students Of SMPS Karang Sari Medan Based On Merdeka Curriculum - Ika Dewi Puspita; Sofia Idawati Lubis; Yunita Mutiara Harahap (Journal of Innovative and Creativity, 2025)
The objectives of this study were: (1) to find out the learning needs of seventh-grade students at SMPS Karang Sari Medan, and (2) to develop printed grammar English materials based on Merdeka Curriculum. This study employed a Research and Development (R&D) design. The respondents were seventh-grade students from SMPS Karang Sari Medan. The research stages were ADDIE (Analysis, Design, Develop, Implementation, Evaluation). These procedures included conducting a needs analysis, designing the outline of printed materials, developing the first draft of the printed materials, receiving feedback from the expert and teacher, evaluating the first draft, and revising the materials. The instruments used are needs analysis questionnaire and teacher's review questionnaire. The data from the needs analysis were analyzed quantitatively using percentage. The data from the expert judgment and teacher's review were analyzed qualitatively using descriptive statistics, and the suggestions were used to revise the first draft of the materials.The final product of this study is printed grammar English materials based on Merdeka Curriculum. The materials consist of two units: "My Daily Activities" and "What Are You Doing?”. Based on the expert judgment, the score for unit 1 and 2 were 4. Based on teacher's review, the score for Unit 1 and 2 were 4. Based on students’ response questionnaire, unit 1 received 3.73 and unit 2 obtained 3.79. These numbers fall in the range score of 3.24 to 4, categorizing the materials as "very good."